Viability of electric vehicles in combined day and night delivery : a total cost of ownership example in Germany - Tessa T. Taefi (European journal of transport and infrastructure research, 2016)
A review of the body of literature yields general indications that electric freight vehicles can improve emissions and costs in off-hour delivery schemes. However, the literature fails to quantify the savings potential in a combined day and off-hours double-shift usage. Hence, this article qualitatively clusters the advantages of electric vehicles in off-hours delivery schemes and provides quantitative exemplary model calculations on the total costs of ownership in single- and double- shift usage. Surprisingly, the calculations contradict the hypothesis that is commonly deduced in the literature that with a higher utilisation, electric vehicles generally become more competitive compared to their conventional siblings. This study finds that electric medium-duty vehicles are only financially competitive at higher mileages, if the savings achieved by lower operational costs are greater than the costs for battery replacements. These become more frequent at higher mileages; hence a long battery warranty is essential when planning to operate EVs in double-shifts. An elasticity analysis finds that further important parameters influencing the competitiveness of medium-duty electric vehicle compared to conventional diesel models are the discount rate, purchase prices, and the cost of diesel fuel. In conclusion, financial subsidies for purchasing freight EVs might lead to higher numbers of these vehicles. However, increasing the per-kilometre cost advantage of electric freight vehicles would support their utilisation, i.e. in combined day and night shifts, and hence would further mitigate the road freight transport emissions in cities.
Keywords: electric vehicles; total cost of ownership; urban freight transport; double-shift; off-hour delivery